Cultural Techniques Assembling Spaces, Texts & Collectives - Dünne, Jörg; Fehringer, Kathrin; Kuhn, Kristina; Struck, Wolfgang (De Gruyter, 2020)
Addressing cultural techniques from different disciplinary perspectives, this volume elaborates upon a concept originally developed in media studies. In a series of case studies, it reconstructs the basic operations of spatialization underlying more complex symbolic artefacts and articulations, which range from techniques of the body to landscapes, from paperwork to encyclopedias, from collections to collectives.